Identifying potential recharge areas of mountain springs through hydrogeological mapping - Thapa, Ram Singh; Subedi, Rajan; Desai, Jayesh; Rijal, Moti Lal; Tiwari, Krishna Raj; Kandel, Pem Narayan (Banko Janakari, 2023)
Springs are the primary source of water for the people inhabiting in the hills and mountain regions of Nepal. Climate variability, climate change, land use change and management factors together with various human activities including haphazard infrastructure development like urbanization and road construction over the recharge area are responsible for drying up of springs in the hills and mountains, especially in the mid-hill region of Nepal. This study attempts to identify the potential recharge zones of the springs within the four catchments viz. Banlekh and Shikharpur of Baitadi and Doti districts, respectively in far-western Nepal, and the Khaste and Begnas of Kaski district in western Nepal through hydrogeological mapping. Hydrogeological Conceptual Model was adopted while identifying the potential recharge areas. We measured the orientation of the rock outcrops, their types, and discontinuities found around the possible recharge areas. We prepared a conceptual hydro-geological layout of the spring-sheds based on the collected data, and delineated the potential recharge areas. We found the potential recharge zone of the Banlekh Springs at hill slopes and bedding plane within the catchment. However, the recharge zone of the Shikharpur Springs was found on the top and beyond the catchment due to the presence of a number of sinkholes. Moreover, the recharge zone of the Thulopadhero Spring was found to be controlled by the orientation of the rocks and fractures found in the unconsolidated sediments within the catchment and beyond the ridge of the escarpment. The rock orientation within the Falekund-Saunepani-Lapsibot Catchment suggests that the potential recharge zone of the springs consists of unconsolidated sediments. The identified potential recharge areas, the observed rainfall, and the discharge data on springs indicated that the recharge areas were more influenced by the local geology.